Application of UV–vis spectrophotometry and chemometrics to investigate adulteration by glucose syrup in Brazilian polyfloral honey - Nunes, Aline; Azevedo, Gadiel Zilto; dos Santos, Beatriz Rocha; Lima, Giuseppina Pace Pereira [UNESP]; Moura, Sidnei; Maraschin, Marcelo (Elsevier, 2024)
The quality control of food in an easy, fast, and low-cost way has been increasingly sought by industry, and methods based on spectroscopy have stood out in recent years. Honey is among the most adulterated foods worldwide, and fraud detection is difficult because it is a chemically complex matrix. In this sense, this study aimed to develop a simple, fast, and cheap method based on UV–vis spectrophotometry coupled to chemometrics for discriminating pure Brazilian polyfloral honey from adulterated ones. For that, 139 real samples of polyfloral honey produced in southern Brazil (Santa Catarina state) were analyzed by UV–vis scanning spectrophotometry (λ 200–800 nm), and a set of 42 samples (i.e., 30%) were intentionally adulterated with glucose syrup (10–60%, w/w). Three wavelength windows were shown to be relevant in the UV–vis spectra (e.g., 260–500 nm, 260–360 nm, and 280–300 nm), and these data sets were further analyzed by principal component analysis (PCA). Pure and adulterated honey samples were better discriminated by computing the 280–300 nm spectral window data (PC1 and PC2 = 98% total variance of the data set). To validate the method, 59 samples produced in southeastern Brazil (São Paulo state) were included in the descriptive model, which allowed identifying pure and adulterated honey again (PC1 + PC2 = 97% of the data set's total variance). Thus, these findings support that UV–vis coupled with PCA proved to be a simple and efficient method to discriminate pure honey from adulterated ones, providing a fast and inexpensive protocol to monitor honey quality.
Keywords: Analytical methods; Food adulteration; Glucose syrup; Sugar adulteration